2015
DOI: 10.1177/1091581815619764
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Toxicological Safety Assessment of an Extract of Olea Europaea L. Leaves (Bonolive™)

Abstract: A battery of toxicological studies was conducted to investigate the genotoxicity and repeated-dose oral toxicity of Bonolive™, a proprietary water-soluble extract of the leaves of the olive tree (Olea europaea L.), in accordance with internationally accepted protocols. There was no evidence of mutagenicity in a bacterial reverse mutation test and in an vitro mammalian chromosomal aberration test nor was any genotoxic activity observed in an in vivo mouse micronucleus test at concentrations up to the limit dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 39 publications
3
29
0
3
Order By: Relevance
“…Results of a study showed that supplementation of olive leaf extract in male and female rats at single dose of 2,000 mg/kg (acute toxicity) and 100, 200, and 400 mg/ kg doses (subacute toxicity) given for 28 days did not result in any toxicity [54]. Water soluble extract of olive leaf was given at the doses of 360, 600, and 1,000 mg/kg/day for 90 days and did not cause any mortality and toxicity [53]. Only one study reported some histological changes such as fatty cytoplasmic vacuolation, necrosis of the hepatocytes, and a slight hemorrhage in both liver and kidneys of rats after the supplementation of olive leaf extract (0.9%) for 6 weeks [56].…”
Section: Safety Of Olive Leaf and Its Extractmentioning
confidence: 89%
See 2 more Smart Citations
“…Results of a study showed that supplementation of olive leaf extract in male and female rats at single dose of 2,000 mg/kg (acute toxicity) and 100, 200, and 400 mg/ kg doses (subacute toxicity) given for 28 days did not result in any toxicity [54]. Water soluble extract of olive leaf was given at the doses of 360, 600, and 1,000 mg/kg/day for 90 days and did not cause any mortality and toxicity [53]. Only one study reported some histological changes such as fatty cytoplasmic vacuolation, necrosis of the hepatocytes, and a slight hemorrhage in both liver and kidneys of rats after the supplementation of olive leaf extract (0.9%) for 6 weeks [56].…”
Section: Safety Of Olive Leaf and Its Extractmentioning
confidence: 89%
“…Although there are strong evidence regarding biological activity of olive leaf extract and its components, there is limited knowledge on their systemic toxicity and reliability [53][54][55]. Toxicity studies show that olive leaf extracts are generally reliable and do not show toxic effect even at high doses [53,54].…”
Section: Safety Of Olive Leaf and Its Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…Newly developed analytical methods and testing since the time these studies were performed have also consistently revealed low levels of other phytocannabinoids (e.g., cannabichromene, cannabigerol, cannabicyclol, and cannabinol) in subsequent batches of this natural extract of the aerial parts of hemp. The tests reported below were conducted according to GLP and OECD guidelines and as previously described by Clewell et al [16]. …”
Section: Methodsmentioning
confidence: 99%
“…All main tests were conducted in accordance with the Organization of Economic Cooperation and Development (OECD) Principles of Good Laboratory Practices (GLP), ENV/MC/CHEM (98)17 [16]. e studies use methods as previously described by Clewell et al [17], Marx et al [18], and Reddeman et al [19] and the methods section partly reproduces our wording. All chemical reagents, solvents, pharmaceuticals, and other chemicals used in the studies were of analytical or pharmaceutical grade.…”
Section: Methodsmentioning
confidence: 99%